Generation of Subgigawatt RF Pulses in Nonlinear Transmission Lines; IEEE Transactions on Plasma Science; Vol. 38, iss. 10 - Rostov V. V. Vladislav Vladimirovich; Bykov N. M. Nikolai; Bykov D. N. Dmitry; Klimov A. I. Aleksey Ivanovich; Koval'chuk O. B. Oleg Borisovich; Romanchenko I. V. Ilya (2010, 2010)
Title screen